2003
DOI: 10.1034/j.1600-0706.2003.12223.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the relation between nutrient supply and biodiversity co‐determined by the type of nutrient limitation?

Abstract: Correlative studies have shown a ‘hump‐backed’ relation between the vegetation N:P ratio and plant species diversity with the highest diversity at balanced N:P ratios (between 10 and 14). We tested the hypothesis that adding growth‐limiting nutrients to mesotrophic grasslands that were in shortage of either N (N:P ratio<10) or P (N:P ratio>14) would lead to an increase of plant diversity. Thereto, we studied the effects of long‐term (11 yr) experimentally increased N and/or P supply on soil nutrient pools, veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 36 publications
4
45
0
3
Order By: Relevance
“…In most terrestrial ecosystems, N-P availability can limit plant growth and affect plant traits, community composition, and biodiversity (Aerts et al 2003;Güsewell et al 2005). Thus, the plant N:P ratio is one of the most simple and effective indicators for assessing limiting elements in plant growth (Koerselman and Meuleman 1996;Güsewell 2004).…”
Section: N-p Stichometry and Nutrient Limitation In Leaves And Soilmentioning
confidence: 99%
See 3 more Smart Citations
“…In most terrestrial ecosystems, N-P availability can limit plant growth and affect plant traits, community composition, and biodiversity (Aerts et al 2003;Güsewell et al 2005). Thus, the plant N:P ratio is one of the most simple and effective indicators for assessing limiting elements in plant growth (Koerselman and Meuleman 1996;Güsewell 2004).…”
Section: N-p Stichometry and Nutrient Limitation In Leaves And Soilmentioning
confidence: 99%
“…Large quantities of C were synthesized through photosynthesis, and N and P were consumed during plant growth, and the concentrations of these elements in habitats directly affect plant growth, thereby limiting ecosystem productivity (Vitousek and Howarth 1991;Elser et al 2010). Many studies showed that the concentrations of available N and P significantly influence plant growth (Aerts et al 2003). High P leaching may lead to limitation of P for plant growth in areas with high rainfall and intense soil erosion, while N might restrict plant growth in those areas with low rainfall, weak soil erosion and thus relatively low P leaching (Aerts et al 2003;Reich and Oleksyn 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 74 grassland plots, Braakhekke and Hooftman (1999) found the highest species richness at vegetation N:P ratios of 10-14, with lower species richness at both higher and lower values. This may be explained by the absence of species adapted to N limitation (indicated by lower N:P ratios; Aerts et al 1992;Shaver and Chapin 1995;Koerselman and Meuleman 1996) or P limitation (higher N:P ratios) in habitats where one of these nutrients is limiting (Braakhekke and Hooftman 1999;Aerts et al 2003). In habitats where resources are balanced, both types of species may be able to persist.…”
mentioning
confidence: 99%